PELATIHAN PENGAJARAN BAHASA INGGRIS INTERAKTIF BAGI GURU PAUD DI DESA SIKUR BARAT - Paris, Atika Salman; Rosyidi, Ahmad Zuhri; Rachman, Sry Anita; Hardianti, Farlina (LPP ARROSYIDIN, 2023)
The aim of this Community Service activity is to help English teachers at the PAUD level in West Sikur village to find, create and apply materials for English teaching and learning activities interactively and according to the children's ages. To achieve this goal, the training method is through training and theoretical deepening. The results of this activity can be described in general as follows: participants were able to understand the theoretical basis for teaching English in kindergarten or PAUD, participants were able to recognize several English songs that could be used for teaching. participants are able to combine songs and movements to help teach English, participants know and try to read simple English stories, participants are able to create simple media to help teach English, participants are able to plan learning activities with fun activities, and participants know and practice several types of games to help with teaching.